Root and root canal morphology of the permanent dentition in a Caucasian population: a cone‐beam computed tomography study. (3rd January 2017) - Martins, J. N. R.; Marques, D.; Mata, A.; Caramês, J.
Abstract: Aim: To investigate in vivo the number of roots, the configuration of the root canal system and the root canal splitting and merging levels in the permanent dentition of a Caucasian population. Methodology: A total of 11 892 teeth were inspected in cone‐beam computed tomography examinations that were collected from a pre‐existing database. The number of roots was identified, and canal configurations were classified according to Vertucci's classification and its supplemental configurations. In addition, the merging and separation positions along the length of the root canal were identified. The Z ‐test was used to analyse the differences between independent groups. A value of P < 0.05 was considered significant. Results: The majority of tooth types had considerable variation in the number of roots and root canal configuration types. Radix entomolaris and paramolaris were rare occurrences. The mesiobuccal root of the maxillary first and second molars had two root canals in 71% and 44% of cases, respectively. Nearly 30% of the mandibular incisors had two root canals. Root canal merging and splitting appeared more often in mandibular teeth. Merging was more common in the middle third of the root canal in the maxillary teeth and in the middle and apical thirds in mandibular teeth. Root canal splitting did not exhibit a tendency, and their position along the length of the root canal varied from tooth to tooth. Conclusion: Clinicians must be aware that each tooth may display several types of root canal configuration. However, a greater variability in root canal configuration was found in maxillary second premolars and in the mesiobuccal roots of maxillary molars. Main root canal merging and splitting may also be expected to occur at any level of the root canal.